The effects of metabolite molecules produced by drinking water-isolated bacteria on their single and multispecies biofilms - Simões, Lúcia C. (2011)
The elucidation of the mechanisms by which diverse species survive and interact in drinking water (DW) biofilm communities may allow the identification of new biofilm control strategies. The purpose of the present study was to investigate the effects of metabolite molecules produced by bacteria isolated from DW on biofilm formation. Six opportunistic bacteria, viz. Acinetobacter calcoaceticus, Burkholderia cepacia, Methylobacterium sp., Mycobacterium mucogenicum, Sphingomonas capsulata and Staphylococcus sp. isolated from a drinking water distribution systems (DWDS) were used to form single and multispecies biofilms in the presence and absence of crude cell-free supernatants produced by the partner bacteria. Biofilms were characterized in terms of mass and metabolic activity. Additionally, several physiological aspects regulating interspecies interactions (sessile growth rates, antimicrobial activity of cell-free supernatants, and production of iron chelators) were studied to identify bacterial species with biocontrol potential in DWDS. Biofilms of Methylobacterium sp. had the highest growth rate and M. mucogenicum biofilms the lowest. Only B. cepacia was able to produce extracellular iron-chelating molecules. A. calcoaceticus, B. cepacia, Methylobacterium sp. and M. mucogenicum biofilms were strongly inhibited by crude cell-free supernatants from the other bacteria. The crude cell-free supernatants of M. mucogenicum and S. capsulata demonstrated a high potential for inhibiting the growth of counterpart biofilms. Multispecies biofilm formation was strongly inhibited in the absence of A. calcoaceticus. Only crude cell-free supernatants produced by B. cepacia and A. calcoaceticus had no inhibitory effects on multispecies biofilm formation, while metabolite molecules of M. mucogenicum showed the most significant biocontrol potential.